Psychosis or Obsessions? Clozapine Associated with Worsening Obsessive-Compulsive Symptoms - Jonathan G. Leung; Brian A. Palmer (Case Reports in Psychiatry)
One underrecognized adverse event of clozapine is the emergence or worsening of obsessive-compulsive symptoms (OCS). OCS, particularly violent thoughts, can be inaccurately described as psychosis and result in a misdiagnosis. We report a case of a 42-year-old man, initially diagnosed with schizoaffective, who was placed on clozapine for the management of “violent delusions.” However, clozapine led to a worsening of these violent thoughts resulting in suicidal ideation and hospitalization. After exploration of the intrusive thoughts and noting these to be egodystonic, clearly disturbing, and time consuming, an alternative diagnosis of obsessive-compulsive disorder (OCD) was made. Clozapine was inevitably discontinued resulting in a significant reduction of the intrusive thoughts without emergence of psychosis or adverse events. While an overlapping phenomenology between OCD and psychotic disorders has been described, clozapine and other antiserotonergic antipsychotics have been implicated with the emergence or worsening of OCS. Unique to our case is that the patient’s obsessions had been treated as psychosis leading to the inadequate treatment of his primary illness, OCD. This case highlights the potential for OCD to masquerade as a psychotic disorder and reminds clinicians that clozapine may worsen OCS.